Incidence, progression and risk factors of age-related macular degeneration in 35–95-year-old individuals from three jointly designed German cohort studies. Issue 1 (4th January 2022) - Brandl, Caroline; Günther, Felix; Zimmermann, Martina E; Hartmann, Kathrin I; Eberlein, Gregor; Barth, Teresa; Winkler, Thomas W; Linkohr, Birgit; Heier, Margit; Peters, Annette; Li, Jeany Q; Finger, Robert P; et al.
Abstract : Objective: To estimate age-related macular degeneration (AMD) incidence/progression across a wide age range. Methods and analysis: AMD at baseline and follow-up (colour fundus imaging, Three Continent AMD Consortium Severity Scale, 3CACSS, clinical classification, CC) was assessed for 1513 individuals aged 35–95 years at baseline from three jointly designed population-based cohorts in Germany: Ko operative Gesundheitsforschung in der R egion A ugsburg (KORA-Fit, KORA-FF4) and A ltersbezogene U ntersuchungen zur G esundheit der U niversität R egensburg (AugUR) with 18-year, 14-year or 3-year follow-up, respectively. Baseline assessment included lifestyle, metabolic and genetic markers. We derived cumulative estimates, rates and risk factor association for: (1) incident early AMD, (2) incident late AMD among no AMD at baseline (definition 1), (3) incident late AMD among no/early AMD at baseline (definition 2), (4) progression from early to late AMD. Results: Incidence/progression increased by age, except progression in 70+-year old. We observed 35–55-year-old with 3CACSS-based early AMD who progressed to late AMD. Predominant risk factor for incident late AMD definition 2 was early AMD followed by genetics and smoking. When separating incident late AMD definition 1 from progression (instead of combined as incident late AMD definition 2), estimates help judge an individual's risk based on age and (3CACSS) early AMD status: for example, for a 65-year old, 3-year late AMD risk with no or early AMD is 0.5% or 7%, 3-year early AMD risk is 3%; for an 85-year old, these numbers are 0.5%, 21%, 12%, respectively. For CC-based 'early/intermediate' AMD, incidence was higher, but progression was lower. Conclusion: We provide a practical guide for AMD risk for ophthalmology practice and healthcare management and document a late AMD risk for individuals aged <55 years.